Fascicle differentiation of upper extremity nerves on high-resolution ultrasound with multimodal microscopic verification - Pušnik, Luka; Radochová, Barbora; Janáček, Jiří; Saudek, František; Serša, Igor; Cvetko, Erika; Umek, Nejc; Snoj, Žiga (Scientific reports, 2025)
This study aimed to compare the fascicular anatomy of upper limb nerves visualized using in situ high-resolution ultrasound (HRUS) with ex vivo imaging modalities, namely, magnetic resonance microscopy (MRM), histological cross-sections (HCS), and optical projection tomography (OPT). The median, ulnar, and superficial branch of radial nerve (n = 41) were visualized in 14 cadaveric upper limbs using 22-MHz HRUS. Subsequently, the nerves were excised, imaged with different microscopic techniques, and their morphometric properties were compared. HRUS accurately differentiated 51-74% of fascicles, while MRM detected 87-92% of fascicles when compared to the referential HCS. Among the compared modalities, HRUS demonstrated the smallest fascicular ratios and fascicular cross-sectional areas, but the largest nerve cross-sectional areas. The probability of a fascicle depicted on HRUS representing a cluster of multiple fascicles on the referential HCS increased with the fascicular size, with some differences observed between the larger median and ulnar nerves and the smaller radial nerves. Accordingly, HRUS fascicle differentiation necessitates cautious interpretation, as larger fascicles are more likely to represent clusters. Although HCS is considered the reference modality, alterations in nerve cross-sectional areas or roundness during sample processing should be acknowledged.
Keywords: senioři; Upper Extremity; mrtvola; Fascicle differentiation; Cadaver; Ulnar Nerve; Middle Aged; mužské pohlaví; Nerve anatomy; nervus radialis; Peripheral nerve imaging; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ultrasonografie; Radial Nerve; ženské pohlaví; Microscopy; Humans; Median Nerve; nervus medianus; lidé středního věku; Ultrasonography; nervus ulnaris; horní končetina; MR neurography; Female; Aged; mikroskopie; lidé; Male